2015
DOI: 10.4317/jced.52298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of low-level laser in improving the symptoms of burning mouth syndrome

Abstract: Background Burning mouth syndrome (BMS) is common conditions that affects menopause women, patients suffer from sever burning sensation. Up to now there is no definitive treatment for this disease. Present study was undertaken to evaluate the efficacy of low-level laser (LLL) in improving the symptoms of burning mouth syndrome. Material and Methods Twenty patients with BMS were enrolled in this study; they were divided in two groups randomly. In the laser group, in each patient, 10 areas on the oral mucosa we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 9 publications
5
82
1
Order By: Relevance
“…Al-Maweri et al (18) made a systemic meta-analysis of the published literature on BMS and LLLT and included results of five randomized clinical trials (16,(19)(20)(21)(22), three uncontrolled clinical trials (23)(24)(25) and two case series (26,27). Sugaya et al (19) have found that LLLT has the same effect as placebo in BMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Maweri et al (18) made a systemic meta-analysis of the published literature on BMS and LLLT and included results of five randomized clinical trials (16,(19)(20)(21)(22), three uncontrolled clinical trials (23)(24)(25) and two case series (26,27). Sugaya et al (19) have found that LLLT has the same effect as placebo in BMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Observing the results of the published RCTs (Arbabi-Kalati et al, 2015;Arduino et al, 2016;Barbosa et al, 2018;Sikora et al, 2018;Spanemberg et al, 2015Spanemberg et al, , 2019Valenzuela & Lopez-Jornet, 2017), LLLT is a successful treatment for management of BMS pain, but there are differences in the design studies and application protocols. With respect to the application protocol, we found an extreme variability in the dose applied: the dose varied from 1 J/cm 2 to 200 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Arbabi‐Kalati et al . studied 20 patients with BMS divided into two groups one treated with laser ( n = 10) (wavelength of 630 nm, 30 mW for 10 s twice a week for 4 weeks) comparing this with a placebo group ( n = 10). The authors found statistically significant changes in the severity of burning sensation ( P = 0·04) and quality of life ( P = 0·01) in favour of laser treatment.…”
Section: Discussionmentioning
confidence: 99%